2016
DOI: 10.1103/physreva.94.013407
|View full text |Cite
|
Sign up to set email alerts
|

Production ofNaCa+molecular ions in the ground state from cold atom-ion mixtures by photoassociation via an intermediate state

Abstract: We present a theoretical analysis of optical pathways for formation of cold ground state (NaCa) + molecular ions via an intermediate state. The formation schemes are based on ab initio potential energy curves and transition dipole moments calculated using effective-core-potential methods of quantum chemistry. In the proposed approach, starting from a mixture of cold trapped Ca + ions immersed into an ultracold gas of Na atoms, (NaCa) + molecular ions are photoassociated in the excited E 1 Σ + electronic state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 73 publications
3
25
0
Order By: Relevance
“…where the expressions in round brackets are 3j symbols, 2S+1 L||Q 2(4) || 2S+1 L is the reduced matrix element of the quadrupole (hexadecapole) moment, and α 0 (iω) and α 2 (iω) are the scalar and tensor components of the dynamic electric dipole polarizability at imaginary frequency of the atom in the 2S+1 L state. The electronic structure data, including the potential energy curves for the ground and excited electronic states, transition electric dipole moments, and matrix elements of the spin-orbit coupling have been calculated for several ion-atom systems relevant for ongoing experimental efforts: (Na+Ca) + (Gacesa et al, 2016;Makarov et al, 2003), (Rb+Ba) + (Knecht et al, 2010;Krych et al, 2011), (Li/Na/K/Rb/Cs+Sr) + , (Rb+Ca) + (Belyaev et al, 2012;Tacconi et al, 2011), (Rb+Yb) + (Lamb et al, 2012;McLaughlin et al, 2014;Sayfutyarova et al, 2013), (Li+Yb) + da Silva Jr et al, 2015;Tomza et al, 2015), (Ca/Sr/Ba/Yb+Cr) + (Tomza, 2015), (Li+Be) + (Ghanmi et al, 2017), (Li+Mg) + (ElOualhazi and , (Li+Ca) + (Saito et al, 2017), (Li+Sr) + (Jellali et al, 2016), (Rb+Ca/Sr/Ba/Yb) + (da Silva Jr et al, 2015), (Na/Ka/Rb+Be) + (Ladjimi et al, 2018), (Li+Li) + (Bouchelaghem and Bouledroua, 2014;Bouzouita et al, 2006;Musia l et al, 2015), (Na+Na) + (Berriche, 2013;Bewicz et al, 2017), (K+K) + (Skupin et al, 2017), (Rb+Rb) + (Jraij et al, 2003;Jyothi et al, 2016), (Cs+Cs) + (Jamieson et al, 2009;Jraij et al, 2005), (Li+Na) + (Li et al, 2015;Musia l et al, 2018), (Li+K) + (Berriche et al, 2005;…”
Section: Atomic Ion and Atommentioning
confidence: 99%
See 3 more Smart Citations
“…where the expressions in round brackets are 3j symbols, 2S+1 L||Q 2(4) || 2S+1 L is the reduced matrix element of the quadrupole (hexadecapole) moment, and α 0 (iω) and α 2 (iω) are the scalar and tensor components of the dynamic electric dipole polarizability at imaginary frequency of the atom in the 2S+1 L state. The electronic structure data, including the potential energy curves for the ground and excited electronic states, transition electric dipole moments, and matrix elements of the spin-orbit coupling have been calculated for several ion-atom systems relevant for ongoing experimental efforts: (Na+Ca) + (Gacesa et al, 2016;Makarov et al, 2003), (Rb+Ba) + (Knecht et al, 2010;Krych et al, 2011), (Li/Na/K/Rb/Cs+Sr) + , (Rb+Ca) + (Belyaev et al, 2012;Tacconi et al, 2011), (Rb+Yb) + (Lamb et al, 2012;McLaughlin et al, 2014;Sayfutyarova et al, 2013), (Li+Yb) + da Silva Jr et al, 2015;Tomza et al, 2015), (Ca/Sr/Ba/Yb+Cr) + (Tomza, 2015), (Li+Be) + (Ghanmi et al, 2017), (Li+Mg) + (ElOualhazi and , (Li+Ca) + (Saito et al, 2017), (Li+Sr) + (Jellali et al, 2016), (Rb+Ca/Sr/Ba/Yb) + (da Silva Jr et al, 2015), (Na/Ka/Rb+Be) + (Ladjimi et al, 2018), (Li+Li) + (Bouchelaghem and Bouledroua, 2014;Bouzouita et al, 2006;Musia l et al, 2015), (Na+Na) + (Berriche, 2013;Bewicz et al, 2017), (K+K) + (Skupin et al, 2017), (Rb+Rb) + (Jraij et al, 2003;Jyothi et al, 2016), (Cs+Cs) + (Jamieson et al, 2009;Jraij et al, 2005), (Li+Na) + (Li et al, 2015;Musia l et al, 2018), (Li+K) + (Berriche et al, 2005;…”
Section: Atomic Ion and Atommentioning
confidence: 99%
“…Numerical calculations of Feshbach resonance spectra have been performed by (Gacesa and Côté, 2017;Idziaszek et al, 2011;Tomza, 2015;Tomza et al, 2015) for a number of ion-atom systems including Yb + +Li, which is the most promising in this respect from the experimental point of view due to the smallest reduced mass. Feshbach resonances were also investigated for collisions involving Cr atoms.…”
Section: A Magnetically Tunable Feshbach Resonancesmentioning
confidence: 99%
See 2 more Smart Citations
“…These laser sources are generally assumed to have a little impact on the dynamics of a single ion in a bath of ultracold atoms. However, it has been shown that the trapping lasers of a magneto-optical trap holding ultracold atoms may lead to an enhancement of the rate of charge-transfer reactions [9,20,32,93,94]. Therefore, laser sources may play a relevant role in the study of a charged impurity in a bath of ultracold atoms.…”
Section: The Role Of External Laser Sourcesmentioning
confidence: 99%